1997
DOI: 10.1016/s0969-2126(97)00216-5
|View full text |Cite
|
Sign up to set email alerts
|

A ‘specificity’ pocket inferred from the crystal structures of the complexes of aldose reductase with the pharmaceutically important inhibitors tolrestat and sorbinil

Abstract: The active site of AR adapts itself to bind tightly to different inhibitors; this happens both upon binding to the inhibitor's hydrophilic heads, and at the hydrophobic and specificity pockets of AR, which can change their shape through different conformational changes of the same residues. This flexibility could explain the large variety of possible substrates of AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
305
1
15

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(344 citation statements)
references
References 37 publications
23
305
1
15
Order By: Relevance
“…In the present study we have further characterized the nature of the interactions between AR inhibitors and the enzyme active site by modeling Tolrestat, Sorbinil and Zopolrestat in the active site of the human holoenzyme. In agreement with crystallographic studies of the human and porcine enzymes [12,16] we have identified a number of apolar residues in the active site that appear to interact with the inhibitors and stabilize them in the active site. To confirm these observations we have quantified the activity of Tolrestat, Sorbinil and Zopolrestat with AR enzymes containing single mutations to these apolar residues.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…In the present study we have further characterized the nature of the interactions between AR inhibitors and the enzyme active site by modeling Tolrestat, Sorbinil and Zopolrestat in the active site of the human holoenzyme. In agreement with crystallographic studies of the human and porcine enzymes [12,16] we have identified a number of apolar residues in the active site that appear to interact with the inhibitors and stabilize them in the active site. To confirm these observations we have quantified the activity of Tolrestat, Sorbinil and Zopolrestat with AR enzymes containing single mutations to these apolar residues.…”
supporting
confidence: 84%
“…Results from several of these studies have indicated that AR inhibitors occupy the active site of the enzyme [12,13,15,16]. Consistent with these findings, site-directed mutagenesis studies have shown that replacing the active-site residue Tyr48 with Phe or His prevented the binding of the AR inhibitor alrestatin.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Although the inhibition assays on our compounds were conducted on rat ALR2, the use of the crystal structure of the human ALR2 for docking study seems reasonable according to the following facts: (i) the crystal structure of rat ALR2 is unknown; (ii) the human and rat sequences of this enzyme are characterized by 85 % identity [16]; (iii) all active-site residues are largely conserved across the ALR2 isoforms sequenced so far [17]. The energy-minimized structure of IDD594 was preliminarily docked into ALR2 to examine how closely the FlexX algorithm can reproduce the binding modes observed in the crystallographic structure.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The hydrogen bonds predicted by FlexX were virtually identical to those found in the crystal structure. It is known from the crystal structures of complexes of ALR2 with carboxylic acid inhibitors that these bind ALR2 with the carboxylate moiety interacting with Tyr48, His110, and Trp111, which are the three key residues involved in binding [17]. Accordingly, compound 3k was expected to bind ALR2 with its carboxylate moiety in a similar position.…”
Section: Molecular Modelingmentioning
confidence: 99%